PENERAPAN QR CODE DALAM PENATAAN GUDANG UNTUK MENGURANGI WAKTU PENCARIAN BENANG di PT X - Sumihartati, Atin; Faujan, M. Akmal; Ayu Setiani R., Puspa; Ibrahim Makki, Achmad; Somantri, Karlina; Dewanto, R. Arief; Totong, - (Texere, 2025)
PT X yarn warehouse have various leftover yarns of different types, colors, and yarn numbers. These leftover yarns can be reused for small-scale production. However, the problem in PT X's yarn warehouse is the difficulty in finding yarns due to their stacked positions and the lack of identification on the yarn piles. As a result, the search time for yarns in the warehouse becomes lengthy, affecting production efficiency. The average search time for one leftover production yarn is 20 minutes and 27 seconds. This study aims to design and implement a QR Code system for organizing raw materials in the yarn warehouse to reduce yarn search time. The research method begins with data collection of the yarns in the warehouse. Next, warehouse organization is carried out by grouping and placing the yarns based on type, color, and yarn number on designated racks. The collected data will form a database in an addressing document in Google AppSheet. Warehouse employees can do scanning the code and be directly directed to a specific page in Google AppSheet, Google Drive, or Google Spreadsheet to quickly obtain yarn location information. The study results show that the implementation of QR Codes leading to a reduction in search time until 98,45%. The average of searching time before the implementation is 20 minutes and 27 seconds and reduced become 19 seconds to locate the yarn position.